Sejarah Pemikiran Ushul Fiqh (Menuju Metode Penemuan Hukum Islam Kontekstual) - Asep Hedi Turmudi (IAIN Ternate, 2019)
For in the social life of some Muslims had difficult carrying certain parts of the process. The presence of the lurch is something reasonable because the book process is formulated by mujtahid in the future, relatively long in a particular situation. And so that in considering re-protected process was formerly supposed to consider re-protected against the fiqh proposal: For seen the result of the study of the proposed fiqh that develops within the party, seen as the basis for the fiqh proposal which process can be changed.